The relationships between supplier and customer involvements towards broiler business performance: An empirical investigation on Malaysian poultry industry - Ariffin, Ahmad Shabudin; Lamsali, Hendrik; Mohtar, Shahimi (2012)
Agriculture is one of the key sectors for international trade that supply foods to the world population.The major contribution of broiler consumption in improving percapita nutrients level is well documented.In the meantime, the importance of supplier and customer involvement within supply chain operations are also well acknowledged. Nonetheless,empirical evidence linking broiler business performance and the aforementioned involvements remains elusive.Hence, this study proposes an investigation over potential relationships between supplier and customer involvements towards broiler business performance. The potential moderating effect of managerial skill levels on the above mentioned relationships is also proposed.A research framework and six hypotheses are then forwarded to further gauge the issues.Plugging the information gap in Malaysian poultry industry and examining the inclusion of customer involvement and managerial skill levels into the model are the focal contribution of this study.Upon completion, the study is expected to be beneficial to relevant authorities, practitioners and interested parties alike.